Liberalisme dan Reformasi Pemikiran Islam: Kajian Genealogis atas Wacana Keagamaan, Gender, dan Politik di Indonesia - Syamsiah, Syamsiah; Prayoga, M. Aditya (Al Mabhats : Jurnal Penelitian Sosial Agama, 2024)
Abstract: This study examines the influence of liberal thought on the development of Islamic religious, social, and political discourse, focusing on how liberal ideas have shaped reform movements within the Muslim world, particularly Indonesia. Employing a qualitative library-research design, the study synthesizes primary and secondary literature books, peer-reviewed journal articles, and mainstream media reports concerning the historical trajectory of liberalism in both Western and Islamic contexts. The analysis traces liberal currents from the classical Islamic intellectual efflorescence of the Abbasid translation movement through to the emergence of the Liberal Islam Network (Jaringan Islam Liberal) in early twenty-first-century Indonesia. Findings indicate that liberalism has functioned less as an imported ideology than as a catalytic framework that intersects with indigenous reformist impulses, producing contextual reinterpretation of sacred texts, expanded discourse on gender justice, and a distinctive Indonesian model of religious moderation (moderasi beragama) that mediates between rigid conservatism and unrestrained secular liberalism. The study contributes a novel Before–After conceptual model and a Multi-Level Framework spanning individual, communal, socio-cultural, and politico-structural levels that maps how liberal ideas are absorbed, contested, and localized within Islamic thought. These findings offer both theoretical refinement for the sociology of religion and practical implications for religious-moderation policy in plural societies. Abstrak: Penelitian ini mengkaji pengaruh pemikiran liberal terhadap perkembangan wacana keagamaan, sosial, dan politik Islam, dengan fokus pada bagaimana gagasan-gagasan liberal telah membentuk gerakan-gerakan reformasi di dunia Muslim, khususnya di Indonesia. Dengan menggunakan desain penelitian kualitatif berbasis pustaka, penelitian ini mensintesis literatur primer dan sekunder buku, artikel jurnal yang telah ditelaah oleh rekan sejawat, dan laporan media arus utama mengenai lintasan historis liberalisme baik dalam konteks Barat maupun Islam. Analisis ini menelusuri arus-arus liberal mulai dari kebangkitan intelektual Islam klasik pada gerakan penerjemahan Abbasiyah hingga munculnya Jaringan Islam Liberal di Indonesia pada awal abad ke-21. Temuan menunjukkan bahwa liberalisme berfungsi bukan sekadar sebagai ideologi impor, melainkan sebagai kerangka kerja katalitik yang bersinggungan dengan dorongan reformis lokal, sehingga menghasilkan penafsiran ulang teks-teks suci yang kontekstual, perluasan wacana tentang keadilan gender, serta model moderasi beragama khas Indonesia yang menjadi jembatan antara konservatisme kaku dan liberalisme sekuler yang tak terkendali. Studi ini menyajikan model konseptual “Sebelum–Sesudah” yang inovatif serta Kerangka Kerja Multi-Tingkat yang mencakup tingkat individu, komunal, sosio-budaya, dan politiko-struktural yang memetakan bagaimana gagasan-gagasan liberal diserap, diperdebatkan, dan dilokalkan dalam pemikiran Islam. Temuan-temuan ini memberikan penyempurnaan teoretis bagi sosiologi agama sekaligus implikasi praktis bagi kebijakan moderasi beragama dalam masyarakat plural.